Acquired demyelination but not genetic developmental defects in myelination leads to brain tissue stiffness changes - Eberle, Dominic; Fodelianaki, Georgia; Kurth, Thomas; Jagielska, Anna; Möllmert, Stephanie; Ulbricht, Elke; Wagner, Katrin; Taubenberger, Anna V.; Träber, Nicole; Escolano, Joan Carles; Van Vliet, Krystyn J.; Guck, Jochen (Brain Multiphysics, 2020)
Changes in axonal myelination are an important hallmark of aging and a number of neurological diseases. Demyelinated axons are impaired in their function and degenerate over time. Oligodendrocytes, the cells responsible for myelination of axons, are sensitive to mechanical properties of their environment. Growing evidence indicates that mechanical properties of demyelinating lesions are different from the healthy state and thus have the potential to affect myelinating potential of oligodendrocytes. We performed a high-resolution spatial mapping of the mechanical heterogeneity of demyelinating lesions using atomic force microscope-enabled indentation. Our results indicate that the stiffness of specific regions of mouse brain tissue is influenced by age and degree of myelination. Here we specifically demonstrate that acquired acute but not genetic demyelination leads to decreased tissue stiffness, which could influence the remyelination potential of oligodendrocytes. We also demonstrate that specific brain regions have unique ranges of stiffness in white and grey matter. Our ex vivo findings may help the design of future in vitro models to mimic the mechanical environment of the brain in healthy and diseased states. The mechanical properties of demyelinating lesions reported here may facilitate novel approaches in treating demyelinating diseases such as multiple sclerosis. Statement of Significance: Mechanical characteristics of a cell's environment can have a profound influence on its biological properties. Neuronal and glial cells are sensitive to mechanical input during development, in disease and regeneration. Sustained tensile strain can promote differentiation of oligodendrocyte progenitor cells into mature oligodendrocytes, which are responsible for the myelination of axons. Changing myelination is an important hallmark in human aging and disease, such as multiple sclerosis. Our hypothesis is that these diseases might be characterized by altered tissue stiffness and that this has an influence on remyelination potential. Here we investigate tissue stiffness profiles of healthy, aged and disease model mice. Manipulating the tissue stiffness might be another promising approach for new treatments.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Atomic force microscopy; Cuprizone; Demyelination; Multiple sclerosis; Shiverer; Tissue stiffness

Amoeboid-like migration ensures correct horizontal cell layer formation in the developing vertebrate retina - Amini, Rana; Bhatnagar, Archit; Schlüßler, Raimund; Möllmert, Stephanie; Norden, Caren; Guck, Jochen (eLife, 2022)
Migration of cells in the developing brain is integral for the establishment of neural circuits and function of the central nervous system. While migration modes during which neurons employ predetermined directional guidance of either preexisting neuronal processes or underlying cells have been well explored, less is known about how cells featuring multipolar morphology migrate in the dense environment of the developing brain. To address this, we here investigated multipolar migration of horizontal cells in the zebrafish retina. We found that these cells feature several hallmarks of amoeboid-like migration that enable them to tailor their movements to the spatial constraints of the crowded retina. These hallmarks include cell and nuclear shape changes, as well as persistent rearward polarization of stable F-actin. Interference with the organization of the developing retina by changing nuclear properties or overall tissue architecture hampers efficient horizontal cell migration and layer formation showing that cell-tissue interplay is crucial for this process. In view of the high proportion of multipolar migration phenomena observed in brain development, the here uncovered amoeboid-like migration mode might be conserved in other areas of the developing nervous system.
CRIS-Team Scopus Importer:2022-08-03
Keywords: amoeboid cell migration; developmental biology; horizontal cells; neuronal lamination; neuronal migration; retina; zebrafish

A switch in pdgfrb+ cell-derived ECM composition prevents inhibitory scarring and promotes axon regeneration in the zebrafish spinal cord - Tsata, Vasiliki; Schweitzer, Christine; Kolb, Julia; Moeckel, Conrad; Boehm, Benjamin; Rosso, Gonzalo; Lange, Christian; Lesche, Mathias; Hammer, Juliane; Kesavan, Gokul; Beis, Dimitris; Guck, Jochen; et al. (Developmental Cell, 2021)
In mammals, perivascular cell-derived scarring after spinal cord injury impedes axonal regrowth. In contrast, the extracellular matrix (ECM) in the spinal lesion site of zebrafish is permissive and required for axon regeneration. However, the cellular mechanisms underlying this interspecies difference have not been investigated. Here, we show that an injury to the zebrafish spinal cord triggers recruitment of pdgfrb+ myoseptal and perivascular cells in a PDGFR signaling-dependent manner. Interference with pdgfrb+ cell recruitment or depletion of pdgfrb+ cells inhibits axonal regrowth and recovery of locomotor function. Transcriptional profiling and functional experiments reveal that pdgfrb+ cells upregulate expression of axon growth-promoting ECM genes (cthrc1a and col12a1a/b) and concomitantly reduce synthesis of matrix molecules that are detrimental to regeneration (lum and mfap2). Our data demonstrate that a switch in ECM composition is critical for axon regeneration after spinal cord injury and identify the cellular source and components of the growth-promoting lesion ECM.In mammals, perivascular cells impede axon regeneration after spinal cord injury through secretion of an inhibitory ECM. Tsata et al. show that in the regeneration-competent zebrafish, myoseptal and perivascular cells promote axon regeneration by depositing a growth-promoting ECM that is deprived of growth-inhibitory matrix molecules.
CRIS-Team Scopus Importer:2022-08-03
Keywords: axon; ECM; fibroblast; myoseptal cells; optoablation; PDGFRβ; perivascular cells; regeneration; spinal cord; zebrafish

Axonal transport, phase-separated compartments, and neuron mechanics - A new approach to investigate neurodegenerative diseases - Noetzel, Martin; Rosso, Gonzalo; Möllmert, Stephanie; Seifert, Anne; Schluessler, Raimund; Kim, Kyoohyun; Hermann, Andreas; Guck, Jochen (Frontiers in Cellular Neuroscience, 2018)
Many molecular and cellular pathogenic mechanisms of neurodegenerative diseases have been revealed. However, it is unclear what role a putatively impaired neuronal transport with respect to altered mechanical properties of neurons play in the initiation and progression of such diseases. The biochemical aspects of intracellular axonal transport, which is important for molecular movements through the cytoplasm, e.g., mitochondrial movement, has already been studied. Interestingly, transport deficiencies are associated with the emergence of the affliction and potentially linked to disease transmission. Transport along the axon depends on the normal function of the neuronal cytoskeleton, which is also a major contributor to neuronal mechanical properties. By contrast, little attention has been paid to the mechanical properties of neurons and axons impaired by neurodegeneration, and of membraneless, phase-separated organelles such as stress granules (SGs) within neurons. Mechanical changes may indicate cytoskeleton reorganization and function, and thus give information about the transport and other system impairment. Nowadays, several techniques to investigate cellular mechanical properties are available. In this review, we discuss how select biophysical methods to probe material properties could contribute to the general understanding of mechanisms underlying neurodegenerative diseases.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Amyotrophic lateral sclerosis; Atomic force microscopy; Brillouin microscopy; Cell mechanics; Neurodegenerative disease; Optical diffraction tomography; Phase separation; Stress granules

Brillouin elastography for non-contact mechanical mapping of spinal cord repair - Czarske, Juergen W.; Schlu¨ßler, Raimund; Möllmert, Stephanie; Guck, Jochen (Optics InfoBase Conference Papers, 2018)
Non-contact, three-dimensional, subcellular measurements of elasticity are presented. We demonstrate a systematic application of Brillouin elastography to quantify the mechanical properties of native larval zebrafish tissues in vivo.
CRIS-Team Scopus Importer:2022-08-03

From Biophysics to Biomedical Physics - Almahayni, Karim; Bachir Salvador, Jana; Moonnukandathil Joseph, Dijo; Yurekli, Nazlican; Möllmert, Stephanie; Möckl, Leonhard (ACS Bio & Med Chem Au, 2024)
The intersection of physics and medicine has long been a fertile ground for innovation, with advances in one field driving breakthroughs in the other. In recent years, the emergence of modern biophysical techniques has provided a toolbox for understanding complex physiological processes across scales. These tools have the potential to revolutionize medical practice, from diagnosis to therapy. However, despite this immense potential, the path from basic biophysical research to clinical translation remains fraught with challenges. This review aims to highlight emerging biophysical tools and their potential applications in medical physics, with a focus on how these innovations can be translated into clinical solutions. We outline a strategic roadmap for bridging the gap between cutting-edge biophysics research and its effective integration into clinical settings, ensuring that these technologies can meaningfully transform patient care.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Biophysics; Clinical biology; Mechanical phenotyping; Medicine; Microscopy; Super-resolution microscopy; Translational medicine

Intracellular Mass Density Increase Is Accompanying but Not Sufficient for Stiffening and Growth Arrest of Yeast Cells - Abuhattum, Shada; Kim, Kyoohyun; Franzmann, Titus M.; Esslinger, Anne; Midtvedt, Daniel; Schluessler, Raimund; Kuan, Hui-Shun; Alberti, Simon; Zaburdaev, Vasily; Guck, Jochen; Möllmert, Stephanie (Frontiers in Bioscience, 2018)
Many organisms, including yeast cells, bacteria, nematodes, and tardigrades, endure harsh environmental conditions, such as nutrient scarcity, or lack of water and energy for a remarkably long time. The rescue programs that these organisms launch upon encountering these adverse conditions include reprogramming their metabolism in order to enter a quiescent or dormant state in a controlled fashion. Reprogramming coincides with changes in the macromolecular architecture and changes in the physical and mechanical properties of the cells. However, the cellular mechanisms underlying the physical-mechanical changes remain enigmatic. Here, we induce metabolic arrest of yeast cells by lowering their intracellular pH. We then determine the differences in the intracellular mass density and stiffness of active and metabolically arrested cells using optical diffraction tomography (ODT) and atomic force microscopy (AFM). We show that an increased intracellular mass density is associated with an increase in stiffness when the growth of yeast is arrested. However, increasing the intracellular mass density alone is not sufficient for maintenance of the growth-arrested state in yeast cells. Our data suggest that the cytoplasm of metabolically arrested yeast displays characteristics of a solid. Our findings constitute a bridge between the mechanical behavior of the cytoplasm and the physical and chemical mechanisms of metabolically arrested cells with the ultimate aim of understanding dormant organisms.
Keywords: yeast; optical diffraction tomography; atomic force microscopy; refractive index; stiffness; liquid solid transition

In vivo assessment of mechanical properties during axolotl development and regeneration using confocal Brillouin microscopy - Riquelme-Guzman, Camilo; Beck, Timon; Edwards-Jorquera, Sandra; Schluessler, Raimund; Mueller, Paul; Guck, Jochen; Sandoval-Guzman, Tatiana; Möllmert, Stephanie (Open Biology, 2022)
In processes such as development and regeneration, where large cellular and tissue rearrangements occur, cell fate and behaviour are strongly influenced by tissue mechanics. While most well-established tools probing mechanical properties require an invasive sample preparation, confocal Brillouin microscopy captures mechanical parameters optically with high resolution in a contact-free and label-free fashion. In this work, we took advantage of this tool and the transparency of the highly regenerative axolotl to probe its mechanical properties in vivo for the first time. We mapped the Brillouin frequency shift with high resolution in developing limbs and regenerating digits, the most studied structures in the axolotl. We detected a gradual increase in the cartilage Brillouin frequency shift, suggesting decreasing tissue compressibility during both development and regeneration. Moreover, we were able to correlate such an increase with the regeneration stage, which was undetected with fluorescence microscopy imaging. The present work evidences the potential of Brillouin microscopy to unravel the mechanical changes occurring in vivo in axolotls, setting the basis to apply this technique in the growing field of epimorphic regeneration.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Axolotl; Cartilage; Confocal Brillouin microscopy; Development; Regeneration

Matrix stiffness mechanosensing modulates the expression and distribution of transcription factors in Schwann cells - Rosso, Gonzalo; Wehner, Daniel; Schweitzer, Christine; Sock, Elisabeth; Guck, Jochen; Shahin, Victor; Möllmert, Stephanie (Bioengineering & Translational Medicine, 2021)
After peripheral nerve injury, mature Schwann cells (SCs) de-differentiate and undergo cell reprogramming to convert into a specialized cell repair phenotype that promotes nerve regeneration. Reprogramming of SCs into the repair phenotype is tightly controlled at the genome level and includes downregulation of pro-myelinating genes and activation of nerve repair-associated genes. Nerve injuries induce not only biochemical but also mechanical changes in the tissue architecture which impact SCs. Recently, we showed that SCs mechanically sense the stiffness of the extracellular matrix and that SC mechanosensitivity modulates their morphology and migratory behavior. Here, we explore the expression levels of key transcription factors and myelin-associated genes in SCs, and the outgrowth of primary dorsal root ganglion (DRG) neurites, in response to changes in the stiffness of generated matrices. The selected stiffness range matches the physiological conditions of both utilized cell types as determined in our previous investigations. We find that stiffer matrices induce upregulation of the expression of transcription factors Sox2, Oct6, and Krox20, and concomitantly reduce the expression of the repair-associated transcription factor c-Jun, suggesting a link between SC substrate mechanosensing and gene expression regulation. Likewise, DRG neurite outgrowth correlates with substrate stiffness. The remarkable intrinsic physiological plasticity of SCs, and the mechanosensitivity of SCs and neurites, may be exploited in the design of bioengineered scaffolds that promote nerve regeneration upon injury.
CRIS-Team Scopus Importer:2021-10-01
Keywords: cell plasticity; extracellular matrix stiffness; mechanosensing; nerve regeneration; neuron; Schwann cell

Mechanical Mapping of Spinal Cord Growth and Repair in Living Zebrafish Larvae by Brillouin Imaging - Schluessler, Raimund; Abuhattum, Shada; Cojoc, Gheorghe; Mueller, Paul; Kim, Kyoohyun; Moeckel, Conrad; Zimmermann, Conrad; Czarske, Jurgen; Guck, Jochen; Möllmert, Stephanie (Biophysical Journal, 2018)
The mechanical properties of biological tissues are increasingly recognized as important factors in developmental and pathological processes. Most existing mechanical measurement techniques either necessitate destruction of the tissue for access or provide insufficient spatial resolution. Here, we show for the first time to our knowledge a systematic application of confocal Brillouin microscopy to quantitatively map the mechanical properties of spinal cord tissues during biologically relevant processes in a contact-free and nondestructive manner. Living zebrafish larvae were mechanically imaged in all anatomical planes during development and after spinal cord injury. These experiments revealed that Brillouin microscopy is capable of detecting the mechanical properties of distinct anatomical structures without interfering with the animal's natural development. The Brillouin shift within the spinal cord remained comparable during development and transiently decreased during the repair processes after spinal cord transection. By taking into account the refractive index distribution, we explicitly determined the apparent longitudinal modulus and viscosity of different larval zebrafish tissues. Importantly, mechanical properties differed between tissues in situ and in excised slices. The presented work constitutes the first step toward an in vivo assessment of spinal cord tissue mechanics during regeneration, provides a methodical basis to identify key determinants of mechanical tissue properties, and allows us to test their relative importance in combination with biochemical and genetic factors during developmental and regenerative processes.
CRIS-Team Scopus Importer:2022-08-03

Nanite: Using machine learning to assess the quality of atomic force microscopy-enabled nano-indentation data - Mueller, Paul; Abuhattum, Shada; Ulbricht, Elke; Taubenberger, Anna V.; Guck, Jochen; Möllmert, Stephanie (BMC Bioinformatics, 2019)
Background: Atomic force microscopy (AFM) allows the mechanical characterization of single cells and live tissue by quantifying force-distance (FD) data in nano-indentation experiments. One of the main problems when dealing with biological tissue is the fact that the measured FD curves can be disturbed. These disturbances are caused, for instance, by passive cell movement, adhesive forces between the AFM probe and the cell, or insufficient attachment of the tissue to the supporting cover slide. In practice, the resulting artifacts are easily spotted by an experimenter who then manually sorts out curves before proceeding with data evaluation. However, this manual sorting step becomes increasingly cumbersome for studies that involve numerous measurements or for quantitative imaging based on FD maps. Results: We introduce the Python package nanite, which automates all basic aspects of FD data analysis, including data import, tip-sample separation, base line correction, contact point retrieval, and model fitting. In addition, nanite enables the automation of the sorting step using supervised learning. This learning approach relates subjective ratings to predefined features extracted from FD curves. For ratings ranging from 0 to 10, our approach achieves a mean squared error below 1.0 rating points and a classification accuracy between good and poor curves that is above 87%. We showcase our approach by quantifying Young's moduli of the zebrafish spinal cord at different classification thresholds and by introducing data quality as a new dimension for quantitative AFM image analysis. Conclusion: The addition of quality-based sorting using supervised learning enables a fully automated and reproducible FD data analysis pipeline for biological samples in AFM.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Atomic force microscopy; Elasticity; Machine learning; Sorting

Small leucine-rich proteoglycans inhibit CNS regeneration by modifying the structural and mechanical properties of the lesion environment - Kolb, Julia; Tsata, Vasiliki; John, Nora; Kim, Kyoohyun; Möckel, Conrad; Rosso, Gonzalo; Kurbel, Veronika; Parmar, Asha; Sharma, Gargi; Karandasheva, Kristina; Abuhattum, Shada; Lyraki, Olga; et al. (Nature Communications, 2023)
Extracellular matrix (ECM) deposition after central nervous system (CNS) injury leads to inhibitory scarring in humans and other mammals, whereas it facilitates axon regeneration in the zebrafish. However, the molecular basis of these different fates is not understood. Here, we identify small leucine-rich proteoglycans (SLRPs) as a contributing factor to regeneration failure in mammals. We demonstrate that the SLRPs chondroadherin, fibromodulin, lumican, and prolargin are enriched in rodent and human but not zebrafish CNS lesions. Targeting SLRPs to the zebrafish injury ECM inhibits axon regeneration and functional recovery. Mechanistically, we find that SLRPs confer mechano-structural properties to the lesion environment that are adverse to axon growth. Our study reveals SLRPs as inhibitory ECM factors that impair axon regeneration by modifying tissue mechanics and structure, and identifies their enrichment as a feature of human brain and spinal cord lesions. These findings imply that SLRPs may be targets for therapeutic strategies to promote CNS regeneration.<br
Keywords: Biophysics; Mechanisms of disease; Spinal cord injury

Zebrafish Spinal Cord Repair Is Accompanied by Transient Tissue Stiffening - Kharlamova, Maria A.; Hoche, Tobias; Taubenberger, Anna; Abuhattum, Shada; Kuscha, Veronika; Kurth, Thomas; Brand, Michael; Guck, Jochen; Möllmert, Stephanie (Biophysical Journal, 2020)
Severe injury to the mammalian spinal cord results in permanent loss of function due to the formation of a glial-fibrotic scar. Both the chemical composition and the mechanical properties of the scar tissue have been implicated to inhibit neuronal regrowth and functional recovery. By contrast, adult zebrafish are able to repair spinal cord tissue and restore motor function after complete spinal cord transection owing to a complex cellular response that includes axon regrowth and is accompanied by neurogenesis. The mechanical mechanisms contributing to successful spinal cord repair in adult zebrafish are, however, currently unknown. Here, we employ atomic force microscopy-enabled nanoindentation to determine the spatial distributions of apparent elastic moduli of living spinal cord tissue sections obtained from uninjured zebrafish and at distinct time points after complete spinal cord transection. In uninjured specimens, spinal gray matter regions were stiffer than white matter regions. During regeneration after transection, the spinal cord tissues displayed a significant increase of the respective apparent elastic moduli that transiently obliterated the mechanical difference between the two types of matter before returning to baseline values after the completion of repair. Tissue stiffness correlated variably with cell number density, oligodendrocyte interconnectivity, axonal orientation, and vascularization. This work constitutes the first quantitative mapping of the spatiotemporal changes of spinal cord tissue stiffness in regenerating adult zebrafish and provides the tissue mechanical basis for future studies into the role of mechanosensing in spinal cord repair.
CRIS-Team Scopus Importer:2022-08-03